PANDANGAN SOSIAL TENTANG DARING DI MASA PANDEMI COVID-19 DI TAPANULI BAGIAN SELATAN - Mardiah, Misbah; Siregar, Sawaluddin (IAIN Padangsidimpuan, 2021)
This research is to find out how the social view of online learning is enforced in the elementary school of Gunung Tua village, Panyabungan District, Mandailing Natal Regency. And this research belongs to field research, which uses a number of data collection models, including observations, in-depth interviews, and documentation methods. Looking at some of the social views of parents of online learning learners is not good and maximal for learners, because there are several factors that the parents of the learners present: many learners are far behind in their thinking progress due to the difficulty of understanding the material described online, the incapableness of learners and parents using technology, some people prevent the down to not having a smartphone or laptop which is a tool to be used as online learning , the limitations of parents to control their ananknya, have problems accessed the internet.